Characteristics of waterflood at low rate in low permeability sandstones based on the CT scanning. Issue 6 (2nd November 2018) - Mo, S.Y.; Lei, Q.; Lei, G.; Gai, S.H.; Liu, Z.K.
ABSTRACT: It is reported that the flooding rate in low permeability sandstones is low and the oil recovery is hard to increase after water breakthrough. Understanding characteristics of waterflood is hence important for the recovery improvement. In this work, flooding tests on low permeability sandstones were conducted. The corresponding flooding characteristics were investigated by means of CT scanning and Nuclear Magnetic Resonance. Effects of irreducible water and different rates were also discussed in detail. Experimental results reveal a piston-like displacement at a low rate in low permeability samples. The saturation profile is steep and almost vertical to the forward direction. The results at a low rate confirm that once water broke through, increasing the flooding rate or flooding time can hardly reduce the remaining oil inside the sample. It is probably due to the high pore-throat ratio proven by rate-controlled mercury. Results also confirm that the presence of initial water enhanced sweep efficiency substantially. On one hand, because water had previously occupied the small pores, the subsequent oil can only invade relatively large pores and became more movable. On the other hand, stable collars can not form due to the steep front, which may suppress the snap-off.